Kebebasan Memilih Pihak dalam Kontrak pada Asas Kebebasan Berkontrak dalam Sewa Menyewa Kamar Tinggal - Annisa Syaufika Yustisia Ridwan; Sa’ida Rusdiana (Jurnal Hukum IUS QUIA IUSTUM, 2018)
One of the scopes of freedom of contract is to freely determine with whom a person makes an agreement. In terms of renting a boarding house in Indonesia, it is often found that the owners of boarding houses only allow Muslim tenants by installing a sign saying "Terima Kost Muslim". The objective of this study was to examine the issues of: first, the meaning of freedom to choose partner in the principle of freedom of contract in the Installation of a Board saying "Terima Kost Muslim", and second, the restriction on freedom to choose partner in boarding house tenancy agreement related to the installation of a Board "Terima Kost Muslim". This was a normative legal research with literature study that aimed to obtain secondary data by reviewing legislation, literature, and other relevant legal materials. The data obtained were then analyzed qualitatively. The conclusions are, first, the meaning and freedom in choosing partner in a boarding house tenancy agreement are that everyone is free to bind him/herself in an agreement by mentioning an offer to a particular party. Second, things that restrict the freedom to choose partner in a boarding house tenancy agreement are the principles of anti-discrimination, legislation and propriety in society